Quasi Contraction of Stochastic Functional Differential Equations (Journal of Partial Differential Equations, 2023)
Using a novel approach, we present explicit criteria for the quasi contractionof stochastic functional differential equations. As an application, some sufficient conditions ensuring the contraction property of the solution to the considered equationsare obtained. Finally, some examples are investigated to illustrate the theory.
Keywords: Quasi contraction; contraction; stochastic functional differential equations.